Impact of agribusiness empowerment interventions on youth livelihoods: insight from Africa - Adeyanju, D.; Mburu, J.; Gituro, W.; Chumo, C.; Mignouna, D.; Mulinganya, N. (Elsevier, 2023)
This study generates evidence to understand the impact of agribusiness empowerment programmes on youth livelihoods in developing countries based on the ENABLE-TAAT programme implemented in Kenya, Nigeria, and Uganda. A multistage sampling technique was used in obtaining primary agribusiness-level data from a sample of 1435 young agripreneurs from the study countries. An Endogenous Treatment Effect Regression (ETER) model was used to assess the impact of programme participation on youth livelihoods (income and food security). Results show that participation significantly increased youth's agripreneurship income by 7% and improved food security by 75% for the pooled analysis. The country disaggregation results show that participation led to a 54% and 37% increase in the income of participants in Nigeria and Uganda, respectively. Also, positive and significant impacts were obtained for food security in the two East African countries. These findings suggest policy interventions or programmes focusing on youth agribusiness empowerment, particularly those that target young actors along different agricultural value chains. The study also suggests interventions geared towards mitigating constraints to credit access and productive resources by young agripreneurs to ease barriers to working capital and business innovation.